2022
DOI: 10.1002/adtp.202200165
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated‐Polymer‐Based Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a promising method for cancer treatment owing to its high spatiotemporal precision and minimally invasive properties. The efficiency of reactive oxygen species (ROS) production by photosensitizers (PSs) directly affects PDT efficacy. Conjugated polymers (CPs) exhibit excellent light‐harvesting capabilities and effective intra‐ and intermolecular energy transfer between CPs and traditional PSs by the “molecular wire effect,” leading to a significant improvement in ROS generation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…It has been clinically applied in tumor treatment with minimal damage to healthy tissues during local treatment. 195 But tumor recurrence and metastasis have restricted the use of PDT in the therapy of solid tumors and advanced cancers. 196 Advanced nanomedicines have recently been designed to enhance the effectiveness of PDT.…”
Section: Combination Therapymentioning
confidence: 99%
“…It has been clinically applied in tumor treatment with minimal damage to healthy tissues during local treatment. 195 But tumor recurrence and metastasis have restricted the use of PDT in the therapy of solid tumors and advanced cancers. 196 Advanced nanomedicines have recently been designed to enhance the effectiveness of PDT.…”
Section: Combination Therapymentioning
confidence: 99%
“…Different from π-conjugated homopolymers and homo-oligomers, π-conjugated copolymers and co-oligomers containing both D and A (D = electron-rich donor and A = electron-deficient acceptor) units can exhibit more intriguing electrical/optical properties, such as near-infrared (NIR) absorption/emission, photothermal (PT), and photodynamic (PD) activities, due to enhanced electron push–pull effect and intra/intermolecular charge-transfer interaction of D–A structure. Given the merits of non-invasivity, spatial selectivity, improved tissue penetration depth, limited drug resistance of NIR-guided photodynamic and photothermal therapies, and appealing advantages of longer circulation time in vivo, less renal clearance, more efficient cellular uptake, stronger capacity in going across blood–brain barrier of fiber-like nanostructures over spherical counterparts, and D–A fiber-like micelles with NIR absorption/emission, PT, and PD activities exhibit promising applications in nanomedicine . Thus, the extension of living CDSA to BCPs containing diverse D–A blocks becomes more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…As a controllable, spatiotemporally precise, and non-invasive treatment approach, phototherapy has attracted a great deal of attention in the ablation of cancer cells, microorganisms, etc. Photodynamic therapy (PDT) and photothermal therapy (PTT) are two typical modalities of phototherapy. Under proper light irradiation, the PDT agent, usually termed the photosensitizer (PS), can produce reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ), superoxide anion radical (O 2 ·– ), etc., with strong oxidizing properties, while the PTT agent can produce heat. Both ROS and high temperature could be utilized to induce cancer cell ablation for tumor therapy.…”
mentioning
confidence: 99%
“…As a controllable, spatiotemporally precise, and non-invasive treatment approach, phototherapy has attracted a great deal of attention in the ablation of cancer cells, microorganisms, etc. Photodynamic therapy (PDT) and photothermal therapy (PTT) are two typical modalities of phototherapy. Under proper light irradiation, the PDT agent, usually termed the photosensitizer (PS), can produce reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ), superoxide anion radical (O 2 ·– ), etc., with strong oxidizing properties, while the PTT agent can produce heat. Both ROS and high temperature could be utilized to induce cancer cell ablation for tumor therapy. It has been confirmed that the combination of PDT and PTT can realize much better treatment efficacy and decrease the risk of recurrence, as compared to PDT or PTT alone. The “1 + 1 > 2” superadditive therapeutic effects have also been observed in certain materials, , because the PDT and PTT processes can be mutually reinforcing.…”
mentioning
confidence: 99%